Study of the visitor concentration and infrastructure on the dynamics of tree collection mortality in Bogor Botanic Gardens - Setyanti, Dwi; Nurhayati,; Pribadi, Didit Okta (Buletin Kebun Raya, 2023)
The death of the tree collection, one of the aspects of the dynamic documented collection, is an indicator of the sustainability of Bogor Botanic Gardens (BBG) landscape management. Visitors and infrastructure factors have yet to be studied directly. The study aimed to examine visitors' concentration and infrastructure development to support the sustainability of tree collections in BBG. The result was obtained by analyzing the dynamics of tree collection mortality to the spatial distribution of visitors' concentration and infrastructure development. The relationship between the tree collection mortality is separately and simultaneously described by linear regression, meanwhile, the variables' contribution is explained using the Analytical Hierarchy Process (AHP) method to be tree management collection review material in BBG. Even though the relationship results are not statistically significant, the areas with high tree collection mortality need more attention in landscape management to sustain BBG tree collections, especially in visitor management and infrastructure development. An overview of landscape management for the sustainability of the BBG collection identified in the framework of the institution's objectives as conservation, research, education, tourism, and environmental services, is hoped that the perspective will become valuable inputfor planning and management of BBG in the future.